Effects of tidal cycles on shorebird distribution and foraging behaviour in a coastal tropical wetland: Insights for carrying capacity assessment. (5th November 2017) - Fonseca, Juanita; Basso, Enzo; Serrano, David; Navedo, Juan G.
Abstract: Wetland loss has driven negative effects on biodiversity by a reduction in potential available habitats, directly impacting wetland-dependent species such as migratory shorebirds. At coastal areas where tidal cycles can restrict food access, the degree to which density of foraging birds is mediated by conspecific abundance or by the available areas is crucial to understanding patterns of bird distribution and wetland carrying capacity. We used the bathymetry of two sectors modeled with two numerical matrices to determine the availability of intertidal foraging areas in relation to tidal level (spring and neap tides), and this information was used to estimate shorebird density and foraging activity throughout the low-tide cycle in a tropical coastal lagoon in northwestern Mexico. Relative to spring tides, an 80% reduction in available foraging areas occurred during neap tides. Overall shorebird abundance was significantly reduced during neap tide periods, with differences between species. Densities of shorebirds increased during neap tides, particularly in one sector, and remained similar throughout the low-tide period (i.e. 4 h) either during spring or neap tides. Time spent foraging was consistently lower during neap-tides relative to spring-tides, especially for Long-billed curlew (44% reduction), Willet (37% reduction) and Black-necked stilt (29% reduction). These decreases in foraging activity when available habitats became reduced can hamper the opportunities of migratory shorebirds to reach their daily energy requirements to survive during the non-breeding season. This study shows that when intertidal habitats are severely reduced an important fraction of shorebird populations would probably be forced to find alternative areas to forage or increase foraging time during the night. Serving an essential function as top-predators, these results can have important implications on carrying capacity assessment for shorebirds at coastal wetlands. Graphical abstract: Highlights: A 80% reduction in intertidal areas occurred during neap tides in a tropical coastal wetland. Shorebird abundance was consistently reduced while densities increased during neap tides. Total time spent foraging during neap-tides was reduced, especially for Long-billed curlew, Willet and Black-necked stilt. These reductions can hamper the opportunities to reach daily energy requirements for shorebirds to survive during the non-breeding season. Our results can have important implications on carrying capacity assessment (for birds) at coastal wetlands.